More on Blameworthiness and Alternative Possibilities - Goddu, G. C. (Journal of moral philosophy, 2006)
Abstract The derivation of the generally held Principle of Alternative Possibilities (PAP), roughly ‘you are morally responsible only if you could do otherwise’, from an even more generally held moral principle, K (for Kant), that roughly speaking ‘ought implies can’, has recently been the focus of significant debate. In this paper I shall argue that by focusing on PAP interpreted in terms of commissions alone an alternative derivation of PAP interpreted in terms of omissions is being overlooked. The advantage of the new derivation is that it avoids many of the criticisms directed at the original derivation.